NEW REINFORCING BAR OF RUP “BMZ” PRODUCTION - N. V. Andrianov; V. A. Matochkin; A. N. Bondarenko; V. A. Tishchenko; I. N. Tihonov; V. Z. Meshkov; V. S. Gumeniuk; G. N. Sudakov (Литьë и металлургия)
The technology of conversion of new kinds of hardware with profile of new type, which will allow to increase considerably the mechanical properties of concrete components and to enhance the steel economy, is considered in the article. The technology of conversion of bale hardware rolled metal, that will allow to increase considerably the solidity and to improve operating abilities of the hardware rolled metal, is also considered.In such a way the given results of work together with NIIZhB and BMZ allowed to receive the new technological decisions, the realization of which along with the steel save will increase the reliability of concrete components of buildings and installations.